Vicarious kinks : s/m in the socio-legal imaginary - Khan, Ummni (University of Toronto Press, 2014)
In Vicarious Kinks, Ummni Khan looks at the mass of claims that film, feminism, the human sciences, and law make about sadomasochism and its practitioners, and the way those claims become the basis for the legal regulation of sadomasochist pornography and practice.